2015
DOI: 10.1177/0009922815594586
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Adverse Reactions in Infants From Medications in Breastmilk

Abstract: The types and rate of adverse drug reactions experienced by breastfed infants whose mothers are taking medications has not been well defined. This article reviews the literature on adverse drug reactions in infants since a previous review in 2002. Case reports and studies of adverse drug reactions in breastfed infants whose mothers were taking a prescribed or over-the-counter medication were selected. Fifty-three case reports and 16 studies were located. Serious acute adverse drug reactions from drugs in breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 52 publications
4
46
0
1
Order By: Relevance
“…In addition to the variability of the daily milk volume noted above, the continuously maturing infant metabolic and excretory pathways and clearance create a situation in which the age of the infant has a great effect on the validity of the RID as an index of safety. Analyses of adverse drug reactions in breastfed infants from drugs in breastmilk show that about two‐thirds of reported adverse reactions occurred during the first month postpartum and more than three‐quarters occur in the first 2 months …”
Section: Relative Infant Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the variability of the daily milk volume noted above, the continuously maturing infant metabolic and excretory pathways and clearance create a situation in which the age of the infant has a great effect on the validity of the RID as an index of safety. Analyses of adverse drug reactions in breastfed infants from drugs in breastmilk show that about two‐thirds of reported adverse reactions occurred during the first month postpartum and more than three‐quarters occur in the first 2 months …”
Section: Relative Infant Dosagementioning
confidence: 99%
“…Analyses of adverse drug reactions in breastfed infants from drugs in breastmilk show that about two-thirds of reported adverse reactions occurred during the first month postpartum and more than three-quarters occur in the first 2 months. 33 Another problem with the use of the RID is that active metabolites are not always considered. For example, in a pooled analysis of plasma concentrations from published studies and one unpublished case, the authors reported 20 mothers taking an average daily dosage of 28 mg of fluoxetine.…”
Section: Pitfalls In the Clinical Use Of The Ridmentioning
confidence: 99%
“…Furthermore, the increased risk at 2–4 weeks of age is reflected in a review of case reports and studies of adverse reactions in breastfed infants of mothers taking medication. In their review, approximately two thirds of reported adverse reactions occurred during the first month PNA, and more than three quarters occurred in the first 2 months PNA (Anderson, Manoguerra, & Valdes, ).…”
Section: Discussionmentioning
confidence: 99%
“…If a particular drug is nonessential and generally used to treat a self‐limiting illness, it may be best to withhold the drug and explore nonpharmacologic supportive treatment options . Even though caution is warranted when prescribing medications to women who breastfeed, it is important to remember that adverse reactions in infants to medications in breast milk are rare, and if they do occur they often require no intervention …”
Section: Choosing a Medicationmentioning
confidence: 99%
“…Thus, it is essential that the safety of taking approved medications while breastfeeding is reviewed when a medication is prescribed. Women can be counseled that the doses the infant receives rarely reach therapeutic levels and that adverse side effects from maternal medications in infants who are breastfed are rare as part of a shared decision‐making process …”
Section: Educationmentioning
confidence: 99%